Study the Anatomical Descriptions and Histological Observations of the Kidney in Golden Eagles (Aquila Chrysaetos) - Abood AL-Agele, Ramzi Abdul ghafoor (The Iraqi Journal of Veterinary Medicine, 2012)
The present study is preliminary investigate of the kidney gross morphology and some histological observations was studied in golden eagle (Aquila Chrysaetus). The anatomical descriptions of the kidneys had revealed a paired kidney and ureters were protrude, flattened and extra-peritoneal organs. The kidney tissue is transverse by major nerve trunks and blood vessels, securing the kidneys tightly in place. Each kidney consists of three lobes: cranial, middle and caudal lobes. The cranial lobe was the largest and wider than the other two lobes and the caudal lobe was appeared similar to middle lobe but little smaller than it. There is no line of demarcation between cortex and medulla as in mammals. The glomerulus consisted of a tightly packed central core of mesangial cells, surrounded by capillary loops. The cytoplasm of the proximal convoluted tubules cells contains condensing vesicles and a large apically situated nucleus. The distal convoluted tubules and collecting ducts were distinguished on a topographical basis revealed that varied slightly in their reactions with PAS stain and appeared as vacuoles or look like vesicles contains secretion from lining epithelial cells of distal convoluted and collecting tubules which appeared diffused in cross section. The cells of distal convoluted tubules and collecting tubules possessed vesicles with a clearly defined coated outer membrane and some had small blebs invaginated membrane. However in this study found vesicles or vacuoles in the lumen of collecting tubules revealed the secreting cells had margins that were often incompletely membrane –bound and continuous with the apical cell margin as if discharging their contents to the tubular lumen.